Penerapan Model Inkuiri Untuk Meningkatkan Minat Siswa Kelas 5 Pada Materi Tema 3 Materi Iklan Elektronik - Hardianti Bahansubu (Peneliti.net, 2023)
Interest in learning is a high heart tendency towards something, passion, desire, Big Indonesian Dictionary (2008: 916). The purpose of this study was to determine the lack of interest and understanding of students in thematic learning grade 5. This study formulates the problem of what causes the lack of interest and understanding of grade 5 students in electronic advertising material, theme 3, sub-theme 3. The target of this research is all 5th grade students of Public Elementary School 2 Moyongkota Baru. The research technique is by observing in class. The results of this study indicate that there are some children who do not understand and are interested in learning theme 3 sub-theme 3 in electronic advertising materials. The influencing factor is the lack of response when learning, it can be seen that students are not interested in this learning process, because the teacher does not involve students in the learning process. From the results of this study it can be concluded that the lack of interest in student learning in learning theme 3 sub-theme 3 in electronic advertising material which is experienced by many grade 5 students of public elementary school 2 Moyongkota Baru) does not understand and distinguish between types of advertisements.